Geodesigning A Game-Theory-Based Compromise Solution Approach in Determining the Cultivation Pattern - Güney, Caner; Ganjali, Narges (Research Square Platform LLC, 2023)
Abstract In basin management, the contradiction between economic development in the basin and its environmental impact is clear. Similarly, in the Marvdasht-Kherameh sub-basin in Fars Province, Iran, there is a deep conflict between different stakeholders in environmental and conservation approaches. Fars province is one of the main agricultural centers of Iran. The agricultural activities of this region have been seriously affected due to the decrease in the amount of water recently. In addition, environmental problems have arisen due to excessive use of fertilizers and pesticides, and the quality of the water has deteriorated. For this reason, determining the appropriate cultivation pattern for agricultural activities in different regions of this province is important in terms of protecting the environment and maintaining economic activity. This causes many stakeholders to seek a consensus-based solution to strike a balance between their respective and often conflicting goals so that agricultural activities can continue in the long term. Hence, a balance must be established between increasing the economic benefits and reducing the negative environmental impacts. One of the mathematical approaches that analyze such conflict situations is game theory. In this study, a suitable cultivation pattern for the Marvdasht-Kherameh basin was tried to be proposed by using game theory and Geospatial Information System approaches together.
Keywords: Sociology and Political Science; Environmental economics; Economics; FOS: Political science; Social Sciences; Optimal Operation of Water Resources Systems; Ocean Engineering; FOS: Law; Epistemology; Environmental science; Engineering; Natural resource economics; Microeconomics; Business; Hydro-Economic Models; Environmental resource management; Political science; Biology; Game theory; Water Science and Technology; Environmental planning; Geography; Contradiction; Paleontology; Agriculture; Structural basin; Water resource management; FOS: Philosophy, ethics and religion; Integrated Management of Water, Energy, and Food Resources; Compromise; Philosophy; Influence of Climate on Human Conflict; Archaeology; Physical Sciences; Environmental Science; Law